Evaluation Of The Achievement Of Hematologists To Transfusion_x000D_ Medicine Education With Self-Assessment Questionnaire In_x000D_ Turkey - (:unkn) unknown (My University, 2020)
Background: Proper clinical use of blood andblood products requires competent theoreticaland practical knowledge of transfusion medicine.The Curriculum Development and StandardDetermination System Medical SpecializationBoard is prepared Hematology SpecialistEducation Core Curriculum in Turkey. In thisstudy, we aimed to determine the access ofhematologists to the learning objectives definedby curriculum for the transfusion medicine andthe factors affecting it.Methods: Hematologists who have beenmembers of Turkish Hematology Society since2013 have been included in the study, Thesurvey questions were prepared based on thecurriculum for transfusion medicine. The studywas applied to hematologists with “surveymonkey” application. The questionnaireconsisted of a competence self-assessment withLikert scale and theoretical multiple-choiceknowledge questions.Results: Of the 213 hematologists, 54 (25%)were included in the study. Hematologists ratedtheir competences in the clinical competenceareas as 3,65 ± 0,73 (median 3,60) as “I knowbut not t a sufficient level”. The participants‘perception of competence was “I know, butnot at a sufficient level’” with an average of3.31 ± 0.84 (median3.5) in the blood bankingfield, while the average in hemapheresis andtransfusion medicine was 4.04 ± 0.63 (median4) as “enough”. In interventional procedures,hematologists stated that their vocationalcompetences were 2,79± 0,92 (median 2,93)on average as “I have an idea- I know, but notenough”. The correct answer to 13 theoreticalquestions was an average of 6,96 ± 1,89(median 7). Hematologists performing bloodrotation felt significantly more competent thanthe physicians who could not do the rotation inthe blood bank, blood banking t(52) = -3.9, p <.001 , transfusion medicine and interventionalcompetence t(52) = -2.2, p = .04 . Physicianswho believed that they are sufficient in theblood banking area, were more confident intransfusion medicine r(54) = .67, p <.001 andmanaging interventional procedures r(54) =.85, p <.001.Conclusion: In this study, hematologistsgenerally felt more competent in subjects suchas transfusion and therapeutic apheresis,which they often think of as not having enoughknowledge in the area of blood banking.Hematologists have been more confident inthe field of transfusion medicine as their yearsof expertise increased, but they did not feelbetter equipped in the fields of blood bankingand interventional competence. The currentresults suggested that hematologists who areexpected to be the blood bank supervisors do notinternalize the area of blood banking, are notstrong in their competence, and do not want towork in this area unless they are required.In hematology education curriculum, positiverevisions in education can be achieved byrevising blood banking curriculum and learningobjectives, standardizing blood center rotationswith content and duration, and support fromonline distance education programs.

Giriş: Kan ve kan ürünlerinin uygun klinik_x000D_ kullanımı, transfüzyon tıbbı konusunda teorik_x000D_ ve pratik bilgi birikimini gerektirir. Türkiye’de_x000D_ Müfredat Geliştirme ve Standart Belirleme Sistemi_x000D_ Tıbbi Uzmanlık Kurulu tarafından, Hematoloji_x000D_ Uzmanlık Eğitimi Temel Müfredatı hazırlanmıştır._x000D_ Bu çalışmada hematologların transfüzyon tıbbı_x000D_ müfredatı ile belirlenen öğrenme hedeflerine_x000D_ ulaşımını ve bu durumu etkileyen faktörleri_x000D_ belirlemeyi amaçladık._x000D_ Metot: 2013 yılından bu yana Türk Hematoloji_x000D_ Derneği üyesi olan hematologlara transfüzyon_x000D_ tıbbı için müfredatı esas alınarak hazırlanan anket_x000D_ “Survey Monkey” uygulaması ile uygulandı._x000D_ Anket, Likert ölçeği ve teorik çoktan seçmeli bilgi_x000D_ soruları ile öz yeterlilik değerlendirmelerinden_x000D_ oluşuyordu._x000D_ Sonuçlar: 213 hematologdan 54’ü (%25)_x000D_ çalışmaya katılmıştır. Hematologların yeterlilik_x000D_ algıları klinik yetkinlik alanlarında ortalama 3,65 ±_x000D_ 0,73 (ortanca 3,60) olarak “Biliyorum ama yeterli_x000D_ düzeyde değil”; kan bankacılığı alanında ortalama_x000D_ 3.31 ± 0.84 (ortanca 3.5) puan ile “biliyorum ama_x000D_ yeterli düzeyde değil”; hemaferez ve transfüzyon_x000D_ tıbbı alanında ise ortalama 4.04 ± 0.63 (ortanca_x000D_ 4) “yeterli” olarak ölçüldü. Girişimsel işlemlerde_x000D_ hematologlar mesleki yeterliliklerinin ortalama_x000D_ 2,79± 0,92 (ortanca 2,93) “Bir fikrim var,_x000D_ biliyorum ama yeterli değil” olarak ifade ettiler._x000D_ 13 teorik sorunun doğru cevabı ortalama 6,96 ±_x000D_ 1,89 idi (ortanca 7). Kan bankası rotasyonu yapan_x000D_ hematologlar yapamayanlara göre kan bankacılığı_x000D_ t(52) = -3.9, p < .001, transfüzyon tıbbı ve girişimsel_x000D_ alanlarda t(52) = -2.2, p = .04 kendilerini çok daha_x000D_ yetkin hissediyordu. Kan bankacılığı alanında_x000D_ yeterli olduğuna inanan hekimler, transfüzyon_x000D_ tıbbında r(54) = .67, p <.001 ve girişimsel_x000D_ işlemlerin r(54) = .85, p <.001yönetiminde de_x000D_ kendilerinden daha eminlerdi._x000D_ Tartışma: Bu çalışmada, hematologlar genellikle_x000D_ kan bankacılığı alanında yeterli bilgiye sahip_x000D_ olmadığını düşünürken transfüzyon tıbbı ve_x000D_ terapötik aferez gibi konularda kendilerini_x000D_ daha yetkin hissetmistirler. Hematologlar,_x000D_ uzmanlık yılları arttıkça transfüzyon tıbbı_x000D_ alanında kendilerine daha fazla güvenmeye_x000D_ başlarken, kan bankacılığı ve girişimsel yeterlilik_x000D_ alanlarında kendilerini hala yeterli donanımda_x000D_ hissetmiyorlardı. Mevcut sonuçlar, hematologların_x000D_ kan bankacılığı alanını içselleştirmediklerini,_x000D_ yetkinliklerinde güçlü olmadıklarını ve gerekli_x000D_ olmadıkça bu alanda çalışmak istemediklerini_x000D_ göstermiştir. Transfüzyon tıbbı müfredatının_x000D_ ve öğrenme hedeflerinin gözden geçirilmesi,_x000D_ kan merkezi rotasyonlarının içerik ve süresinin_x000D_ standartlaştırılması ve çevrimiçi uzaktan eğitim_x000D_ programları ile desteklenmesi hematoloji eğitimine_x000D_ olumlu katkılar sağlayabilir.
Türkiye´de Hematologların Transfüzyon Tıbbı Uzmanlık Eğitim Hedeflerine Ulaşımının Öz Yeterlilik Anketi ile Değerlendirilmesi